Multiwavelength Erbium Fiber Laser based on Rayleigh Backscattering incorporating Lyot Filter - David A.P.; Yusoff N.M.; Sulaiman A.H.; Ismail A.; Abdullah F.; Jamaludin M.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Backscattering; Fiber lasers; Fibers; Light polarization; Amplifier power; Erbium-doped fiber amplifiers; Half waveplate; Lasing lines; Lyot filters; Multi wavelength fiber laser; Multiwavelength spectra; Nonlinear polarization rotation; Quarter waveplates; Rayleigh backscattering; Erbium doped fiber amplifiers